2009
DOI: 10.2188/jea.je20080081
|View full text |Cite
|
Sign up to set email alerts
|

Risk Charts Illustrating the 10-year Risk of Myocardial Infarction among Residents of Japanese Rural Communities: The JMS Cohort Study

Abstract: BackgroundRisk charts that depict the absolute risk of myocardial infarction (MI) for each combination of risk factors in individuals are convenient and beneficial tools for primary prevention of ischemic heart disease. Although risk charts have been developed using data from North American and European cardiovascular cohort studies, there is no such chart derived from cardiovascular incidence data obtained from the Japanese population.Methods and ResultsWe calculated and constructed risk charts that estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Large-scale cohort studies have developed a number of risk prediction tools of cardiovascular disease. [4][5][6][7][8][9][10][11][12][13][14][15] However, these risk prediction tools were mainly derived from studies carried out in Western populations and few risk prediction tools are developed among general Japanese populations. The NIPPON DATA 80 derived a cardiovascular risk prediction tool, in which age, sex, systolic blood pressure, glucose levels, total cholesterol and smoking habits were included as risk factors, using data obtained from a 19-year prospective cohort study of general Japanese populations, although the outcome of NIPPON DATA 80 risk charts was death from cardiovascular causes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale cohort studies have developed a number of risk prediction tools of cardiovascular disease. [4][5][6][7][8][9][10][11][12][13][14][15] However, these risk prediction tools were mainly derived from studies carried out in Western populations and few risk prediction tools are developed among general Japanese populations. The NIPPON DATA 80 derived a cardiovascular risk prediction tool, in which age, sex, systolic blood pressure, glucose levels, total cholesterol and smoking habits were included as risk factors, using data obtained from a 19-year prospective cohort study of general Japanese populations, although the outcome of NIPPON DATA 80 risk charts was death from cardiovascular causes.…”
Section: Discussionmentioning
confidence: 99%
“…The NIPPON DATA 80 derived a cardiovascular risk prediction tool, in which age, sex, systolic blood pressure, glucose levels, total cholesterol and smoking habits were included as risk factors, using data obtained from a 19-year prospective cohort study of general Japanese populations, although the outcome of NIPPON DATA 80 risk charts was death from cardiovascular causes. 5 The Jichi Medical School (JMS) cohort study developed 10-year risk prediction tools for incidence of myocardial infarction 14 and stroke, 15 in which age, sex, systolic blood pressure, diabetes, total cholesterol and smoking habits were included as risk factors, using data obtained from a population-based prospective study of general Japanese populations. The present analysis from the Hisayama study developed a new risk prediction tool for incidence of cardiovascular disease in a general population of Japanese using similar risk factors used in the previous observational studies of Japanese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JALS study group developed a prediction tool for acute myocardial infarction (AMI), but their prediction period was relatively short (five years) 14) . The JMS-cohort study chart was also targeted for AMI, but the population was limited to rural residents 15) . These tools are all associated with some advantages and disadvantages.…”
Section: Definition Of Ckdmentioning
confidence: 99%
“…Because approximately 66% of the Japanese population lives in urban areas according to 2006 Japanese Census 48) , this is an important feature of our analysis. Interestingly, the JMS cohort and JALS reported that the crude incidence of AMI was 0.68 and 0.60 per 1000 person-years, respectively 11,14,15,49) . On the contrary, the crude incidence of AMI in the Suita study was 1.40 50) .…”
Section: Fundingmentioning
confidence: 99%